Objective Measurement of Effective Message through Photograph among the Public - Adzrool Idzwan Hj. Ismail; Kamarudzaman Md. Isa; Mustaffa Halabi Hj. Azahari; Roziah Mohd Janor (ITB Journal Publisher, LPPM ITB, 2013)
'Photograph' is to an extent very close with visual representation, which consists as a part of an act of seeing which establishes places and subject matters in the surrounding world. These would in part, described in words and explained such paradigm. However, it's still yet lacking in the content of the emotional experience as a total. Such form of images plays as an important role, yet lacking realization, as it is also a part of a design committee in society. The act of seeing which establishes our place in the surrounding world, we can describe the world using words, but words can never describe the emotional experience in total. What does visual really mean? How is visual measured? As an observer, how can we define whether the message and the meaning of a particular visual is delivered and understood along with the information it carries? Those three questions play important roles especially with the rapid growth of technology, which contributes to the development of human knowledge especially in the art industries. This paper explores the problems in understanding of photography imageries and their impact to the society.